2016
DOI: 10.3892/mmr.2016.4961
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 receptors are involved in the regulation of fibrogenesis during skin wound repair in mice

Abstract: Studies have shown that cannabinoid CB2 receptors are involved in wound repair, however, its physiological roles in fibrogenesis remain to be elucidated. In the present study, the capacity of cannabinoid CB2 receptors in the regulation of skin fibrogenesis during skin wound healing was investigated. To assess the function of cannabinoid CB2 receptors, skin excisional BALB/c mice were treated either the cannabinoid CB2 receptor selective agonist, GP1a, or antagonist, AM630. Skin fibrosis was assessed by histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“… 65 Furthermore, it seems that the activation of CB2 receptors reduces the fibrotic formation in a wound model in mice through the modulation of TGF-β in late stages of the wound healing process. 66 This anti-fibrotic effect mediated by CB2 receptor activation has been confirmed in CB2 receptor knockout mice studies. 67 On the other hand, CB1 receptors activation promotes a fibrotic response in mice.…”
Section: Discussionmentioning
confidence: 76%
“… 65 Furthermore, it seems that the activation of CB2 receptors reduces the fibrotic formation in a wound model in mice through the modulation of TGF-β in late stages of the wound healing process. 66 This anti-fibrotic effect mediated by CB2 receptor activation has been confirmed in CB2 receptor knockout mice studies. 67 On the other hand, CB1 receptors activation promotes a fibrotic response in mice.…”
Section: Discussionmentioning
confidence: 76%
“…The post-injury treatment of mice was according to previously published methods [ 8 , 22 ]. Briefly, mice that underwent surgery were randomly divided into four groups (vehicle group, JWH133 group, GP1a group, and AM630 group; 25 mice in each group) and administered an i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Several research groups have shown that the selective activation of CB2R can attenuate pro-inflammatory M1 macrophage polarisation and increase anti-inflammatory M2 polarisation [ 18 21 ]. However, considering CB2R inhibits fibrosis [ 8 , 22 , 23 ] while M2 promotes fibrosis [ 17 , 24 ], the activation of CB2R to increase levels of M2 macrophages appears contradictory. Therefore, we hypothesised that the activation of CB2R to attenuate inflammation is not achieved by up-regulating M2 macrophage levels.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the activation of cannabinoid receptor 2 (CB2R), a specific metabotropic receptor of the endocannabinoid system (ECS), reduces inflammation in cerebral ischemic injury, acute myocardial infarction, nephropathy, and cystitis 14 17 . Moreover, CB2R activation also attenuates hepatic and skin fibrosis in mouse models 18 , 19 . Activating of CB2R with agonist inhibits the development of renal fibrosis, and a CB2R antagonist blunts this beneficial anti-fibrotic effect in a unilateral ureteral obstruction (UUO) mouse model 20 .…”
Section: Introductionmentioning
confidence: 97%